2009
DOI: 10.3928/01484834-20090610-03
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multidisciplinary Course in Cultural Competence for Nursing and Human Service Professions

Abstract: A multidisciplinary teaching model was used to develop a pilot course for students in the human service professions of nursing, education, and social work to gain additional knowledge and skills in providing diverse clients with culturally appropriate services during field and clinical experiences. This article focuses on the process of developing a multidisciplinary course in cultural competence that is consistent with a university mission to prepare students for leadership and service in an increasingly dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
0
13
0
10
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Due to extensive evidence of the effectiveness of this framework, nurse educators should consider using it when structuring their courses. The timing of the course in the curriculum also needs to be considered.…”
Section: Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Due to extensive evidence of the effectiveness of this framework, nurse educators should consider using it when structuring their courses. The timing of the course in the curriculum also needs to be considered.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Some studies that used this model showed its effectiveness in guiding teaching and learning methods, but there is a need for further research identifying predictors of cultural competence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Many approaches were noted in the literature related to cultural competence in the curriculum, and are summarized as follows: the need to critically evaluate implementation and evaluation methods of cultural concepts in the curriculum, [4,9,10,12,15,17,38,39] use of a stand-alone course on culture in the curriculum, [22,30] integration of cultural concepts throughout the curriculum, [12,13,40] use of service learning projects and cultural immersion projects to increase cultural competence, [11,12,[41][42][43][44][45][46][47] lack of qualified faculty members to teach cultural concepts, [23,48] need for course material to adapt to the changing learning needs of students, [45] and international collaboration among teaching institutions to teach cultural competence. [6,35,39,49] While the above note...…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the following three factors were targeted as issues to be addressed regarding the provision of nursing care to foreign patients: (1) the language barrier; [9][10][11] (2) the cultural competence of the health care providers; [12][13][14] and (3) the medical or health insurance system [15][16][17]. To tackle the above issues, we developed the education program [13,[18][19][20][21][22][23][24][25]. The purpose of the program was to provide nurses with information on providing nursing care to foreign patients, and improve the nurses' self-confidence.…”
Section: Development and Implementation Of The Education Programmentioning
confidence: 99%
“…Une revue systématique (Allen, 2010) a aussi été conservée pour la même raison. Ensuite, une revue narrative (Long, 2012) et cinq études primaires (Allen, Brown, Duff, Nesbitt, et Hepner, 2013;Aponte, 2012;Cuellar, Brennan, Vito, et de Leon Siantz, 2008;Hawala-Druy et Hill, 2012;Munoz, DoBroka, et Mohammad, 2009) ont été retenues parmi plus de 60 articles pour la rigueur et la précision dans leur description d'une activité d'enseignement mise à l'essai avec des étudiantes au premier cycle en sciences infirmières. L'analyse des écrits est présentée selon les quatre thèmes suivants : les stratégies d'intégration, les activités d'enseignement, la réflexion sur soi et l'apprentissage dans l'action.…”
Section: Recension Des éCritsunclassified
“…Pour certaines, ces activités sont condensées dans un seul cours (Allen et al, 2013;Aponte, 2012;Hawala-Druy et Hill, 2012;Munoz et al, 2009). La durée des cours décrits dans les études citées précédemment variait de deux à quatre heures par semaine pour une période de 7 à 15 semaines.…”
Section: Stratégie D'intégrationunclassified